A Breast Reconstruction Using a Breast Prosthesis and Capsular Flap for a Lymphocele Patient. Issue 10 (October 2017) - Yano, Tomoyuki; Shimizu, Daisuke; Ishii, Yoshitaka; Ito, Osamu; Sawaizumi, Masayuki
Abstract : Summary: We encountered a very rare condition where the patient had a lymphocele under the skin envelope of the breast following mastectomy during the course of breast reconstruction with a tissue expander. The incidence rate of axillary lymphoceles is reported as 2.2–50% in breast cancer patients, but there have been no reports mentioning lymphoceles under the breast skin during the course of breast reconstruction with a prosthesis. The patient had a lymphocele in the lower lateral part of the breast following mastectomy and had multiple cellulitis-like inflammations. These inflammations were treated with conservative therapy such as administration of antibiotics, resting, and cooling. After 6 months of the initial surgery, the patient underwent complete resection of the lymphocele, preventative elimination of a possible lymphatic leakage, and breast reconstruction using a prosthesis combined with a capsular flap. The capsular flap is a transposition flap that uses capsular tissue around the expander to cover adjacent thinned skin. There were no postoperative complications such as breast skin necrosis, exposure of the prosthesis, or recurrence of the lymphocele and cellulitis. The patient had a successful breast reconstruction even though a lymphocele of the breast was observed. Even though a patient may have a lymphocele in the breast following mastectomy, with careful resection of the lymphocele, complete elimination of possible lymphatic leakage, and by performing the capsular flap technique, complete breast reconstruction with a breast prosthesis may be successful.